Experimental and theoretical study of matrix-assisted refolding - Zhang, Chun Yan (2010)
Inclusion Bodies (IBs), which are dense, insoluble, biologically inactive protein aggregates, are commonly produced in industrial scale protein expression. Matrix-assisted refolding (MAR), or On-Column Refolding (OCR), is a process which transforms IBs from their aggregated form to the correctly folded, biologically active, native form with the assistance of a chromatographic column. In this project, the mathematical model of MAR was developed by combining adsorption, dispersion and reaction kinetics in a set of Partial Differential Equations (PDEs). A FORTRAN programme was written to solve the set of PDEs and simulate the MAR process. The adsorption isotherms involved in the model were experimentally measured for Recombinant Human α-FetoProtein (rhAFP, or AFP in short), while the refolding and aggregation reaction kinetic constants were derived from the literature. With all parameters available, both Bovine Serum Albumin (BSA) and AFP refolding processes were simulated using the FORTRAN programme, and the simulation results agree well with the literature experimental data. It was proved in the simulation that, MAR can achieve a much higher productivity and lower solvent consumption rate than the conventional dilution refolding. Furthermore, it was also found from the simulation that, the refolding selectivity increases with longer refolding duration, but decreases with higher feed protein concentration. The programme can be used for protein refolding yield monitoring, inlet protein concentration optimization, and optimum refolding duration selection prior to on-column refolding experiments.